Advancing our understanding of the inheritance and transmission of pectus excavatum - Horth, Lisa; Stacey, Michael W.; Proud, Virginia K.; Segna, Kara; Rutherford, Chelsea; Nuss, Donald; Kelly, Robert E. (Journal of Pediatric Genetics, 2012)
Pectus excavatum is the most common congenital chest wall abnormality expressed in children, yet its inheritance is poorly understood. Here we present the first comprehensive assessment of the inheritance of this disorder. After evaluating 48 pedigrees and 56 clinical traits of probands and family members, we find strong evidence of autosomal recessive, genetic control for this disorder. Additionally there is likely more than one pectus disease-associated allele, as well as a relatively large number of disease allele carriers in the human population. Some clinical traits appear important and may serve as reliable indicators for predicting the likelihood of pectus excavatum in children before severe symptoms present. Quantifying sex-ratio bias in probands demonstrates a highly significant male bias associated with pectus excavatum. When combined with pedigree data, sex-bias is indicative of sex-linked, sex-limited, and/or epigenetic control such as X-inactivation, reiterating a point made with pedigrees alone, which is that more than one mutation is likely responsible for this disorder.
Keywords: Disease; heritable; genetic; association study